2019
DOI: 10.1016/j.jbef.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Overconfidence and disposition effect in the stock market: A micro world based setting

Abstract: Modern financial theory relies on the rationality assumption of investors even though, evidence suggests that market investors are affected by behavioural biases such as overconfidence and disposition effect. Overconfident investors perceive situations better than what they actually are, while investors exhibiting disposition effect tend to dispose winner shares and keep loser ones. However there is not clear causal relationship between both biases. We contribute to the literature about overconfidence and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 35 publications
0
23
0
3
Order By: Relevance
“…The statements formulated to measure the overconfidence bias express the notion of Trejos et al (2019) that overconfidence manifests itself in two ways: in decision making, when the decision maker overestimates his ability to plan an action; and after making a decision. The indicators OC2, OC4, OC5, and OC7 aim at identifying whether managers overestimated their decision-making ability at a given time, leading them to believe that they had comparative advantages in their companies; the items OC1, OC3, OC8, and OC9 aim at identifying the managers who think they can better predict the future well over the current situation allows, both in decision making and decision making in investment in real assets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The statements formulated to measure the overconfidence bias express the notion of Trejos et al (2019) that overconfidence manifests itself in two ways: in decision making, when the decision maker overestimates his ability to plan an action; and after making a decision. The indicators OC2, OC4, OC5, and OC7 aim at identifying whether managers overestimated their decision-making ability at a given time, leading them to believe that they had comparative advantages in their companies; the items OC1, OC3, OC8, and OC9 aim at identifying the managers who think they can better predict the future well over the current situation allows, both in decision making and decision making in investment in real assets.…”
Section: Methodsmentioning
confidence: 99%
“…Overconfidence bias was first addressed in cognitive psychology research and experiments (Trejos et al, 2019). It was found that individuals overestimate their ability to predict the future and the precision of the information they have in a given situation, that is, individuals with the bias of overconfidence overestimate their decision-making ability in real situations (Tversky & Kahneman, 1974;Pompian, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrikogiannopoulou and Papakonstantinou (2018) find that the effect of disposal was driven primarily by unrealized capital gains and that the higher the power when demand price elasticity was low, validating the disposition of investors holding loss-making stocks. Trejos, van Deemen, Rodríguez, and Gomez (2019) an exploratory analysis of demographic factors and investor performance characteristics shows that investors with short investment horizons, more experience and investment in large-cap stocks are more susceptible to overconfidence. At last, Da, Engelberg, and Gao (2015) points out that the questionnaire method cannot be used in high-frequency data, and that results will become increasingly unreliable if the response rate in the survey is high or the motivation for telling the truth is low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Pompian, 2012) Kepercayaan diri yang berlebihan pada investor juga menunjukkan dirinya berada pada posisi diatas rata dalam keuangan sehingga mampu menentukan keputusan investasi dengan baik. (Trejos et al, 2019). Jelas, perilaku bias kepercayaan diri yang berlebihan memberikan dampak pada keputusan investasi.…”
unclassified